2019
DOI: 10.5334/ijic.4177
|View full text |Cite
|
Sign up to set email alerts
|

A Realist Synthesis of Literature Informing Programme Theories for Well Child Care in Primary Health Systems of Developed Economies

Abstract: Introduction: Well-child Care is the provision of preventative health care services for children and their families. The approach, however, to the universal provision of those services is contentious. Methods: We undertook a realist synthesis to enhance understanding of the theoretical mechanisms driving Well-child Care by searching for published and grey literature from multiple databases. Findings: Well-child Care is re-conceptualised as an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 68 publications
(78 reference statements)
0
7
0
Order By: Relevance
“…Parental health literacy might reduce the children's use of General Practitioner and Emergency health services (Perrin et al, 2020). So, Garg et al (2019) have suggested that early education programs should globally focus on increasing parental health literacy for the sake of child health and safety.…”
Section: Health Literacymentioning
confidence: 99%
See 1 more Smart Citation
“…Parental health literacy might reduce the children's use of General Practitioner and Emergency health services (Perrin et al, 2020). So, Garg et al (2019) have suggested that early education programs should globally focus on increasing parental health literacy for the sake of child health and safety.…”
Section: Health Literacymentioning
confidence: 99%
“…, 2020). So, Garg et al . (2019) have suggested that early education programs should globally focus on increasing parental health literacy for the sake of child health and safety.…”
Section: Introductionmentioning
confidence: 99%
“…39,44 With the Critical Appraisal Skills Programme, study quality was considered low if half or less than half of the criteria were met, medium if more than half but less than three-quarters of the criteria were met, and high if most were met. 46 The scores were produced, summed and ranked high and medium quality for both randomised and non-randomised studies.…”
Section: Quality Appraisalmentioning
confidence: 99%
“…The integrated services that have emerged are delivered by various combinations of health care providers, social care practitioners, community advocates, and public institutions, and situated in a range of central and localised clinical and locality-based settings (20,21). Together they share the aim of providing widely accessible health and social care for CYP and their families that can help treat and manage acute and chronic health care alongside the necessary social support that can help mitigate the social determinants of ill-health such as poor housing, domestic violence, or food poverty (21,22). However, despite widespread investment in these systems in countries such as the United Kingdom (23), evidence of the benefits of integrating health and social care remains inconsistent, particularly amongst underserved CYP (24,25): Little is known of which integrated models are most effective, including the precise combination of services, the specific outcomes they improve, or the impact on the surrounding health economy (26,27).…”
Section: Introductionmentioning
confidence: 99%
“…The integrated services that have emerged are delivered by various combinations of health care providers, social care practitioners, community advocates, and public institutions, and situated in a range of central and localised clinical and locality-based settings (20, 21). Together they share the aim of providing widely accessible health and social care for CYP and their families that can help treat and manage acute and chronic health care alongside the necessary social support that can help mitigate the social determinants of ill-health such as poor housing, domestic violence, or food poverty (21, 22).…”
Section: Introductionmentioning
confidence: 99%